Hyperthyroidisme pada Kehamilan - Robby Cahyo Nugroho (Puslitbang Sinergis Asa Professional, 2021)
Hyperthyroidism is defined by abnormally high levels of thyroid hormones caused by increased synthesis and secretion of thyroid hormones from the thyroid gland. Physiological changes in pregnancy affect the function of the thyroid gland. The sharp increase in human chorionic gonadotropin (hCG) from early pregnancy stimulates the thyroid gland to increase thyroid hormone production. hCG is a glycoprotein synthesized and released from the placenta, and stimulates the TSH receptor due to its structural similarity to TSH. Normal pregnancy produces a number of important physiological and hormonal changes that alter thyroid function. These changes mean that laboratory tests of thyroid function should be interpreted with caution during pregnancy. Thyroid function tests change during pregnancy due to the influence of two main hormones: human chorionic gonadotropin (hCG), the hormone measured in pregnancy tests and estrogen, the main female hormone. The treatment of choice in pregnancy is antithyroid drugs (ATD). These drugs are effective in controlling maternal hyperthyroidism, but they all cross the placenta, thus requiring careful management and control during the second half of pregnancy taking into account the risk of fetal hyperthyroidism or hypothyroidism. An important aspect in early pregnancy is that the main side effect of taking ATD at 6-10 weeks of gestation is birth defects which can develop after exposure to the types of ATD available and may be severe. This review focuses on the management of overt hyperthyroidism in pregnancy, including the etiology and incidence of the disease, how the diagnosis is made, the consequences of untreated or inadequately treated disease, and finally how to treat overt hyperthyroidism in pregnancy. This review discusses the etiology, pathophysiology, and initial evaluation of hyperthyroidism in pregnancy, followed by a discussion of its treatment, management, and complications.